2007
DOI: 10.1371/journal.pone.0000829
|View full text |Cite
|
Sign up to set email alerts
|

Beringian Standstill and Spread of Native American Founders

Abstract: Native Americans derive from a small number of Asian founders who likely arrived to the Americas via Beringia. However, additional details about the intial colonization of the Americas remain unclear. To investigate the pioneering phase in the Americas we analyzed a total of 623 complete mtDNAs from the Americas and Asia, including 20 new complete mtDNAs from the Americas and seven from Asia. This sequence data was used to direct high-resolution genotyping from 20 American and 26 Asian populations. Here we des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

46
602
4
40

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 547 publications
(705 citation statements)
references
References 45 publications
46
602
4
40
Order By: Relevance
“…20 In addition, complete mtDNA genome studies have shown that all pan-American mtDNA haplogroups reveal entry times of 15-18 Ka, which are suggestive of a concomitant post-Last Glacial Maximum arrival from Beringia with early Amerindians. [39][40][41][42] As for the question whether the Q1a3*-M346 was present in South Siberia in the post-Last Glacial Maximum, we can report that divergence time estimate for South Siberian versus Chinese/North Pakistan Q1a3*-M346 haplotypes is 15.29 ± 5.49 Ka, thus supporting the idea for the real presence of Q1a3*-M346 in South Siberia in those times.…”
Section: Discussionsupporting
confidence: 65%
“…20 In addition, complete mtDNA genome studies have shown that all pan-American mtDNA haplogroups reveal entry times of 15-18 Ka, which are suggestive of a concomitant post-Last Glacial Maximum arrival from Beringia with early Amerindians. [39][40][41][42] As for the question whether the Q1a3*-M346 was present in South Siberia in the post-Last Glacial Maximum, we can report that divergence time estimate for South Siberian versus Chinese/North Pakistan Q1a3*-M346 haplotypes is 15.29 ± 5.49 Ka, thus supporting the idea for the real presence of Q1a3*-M346 in South Siberia in those times.…”
Section: Discussionsupporting
confidence: 65%
“…10,13,[31][32][33] In this connection, we consider challenging the assertion by Tamm et al 34 : 'A novel demographic scenario of relatively recent gene flow from Beringia to deep into western Siberia (Samoyed-speaking Selkups) is the most likely explanation for the phylogeography of haplogroup A2a, which is nested within an otherwise exclusively Native American A2 phylogeny'. The single Selkup mitogenome, attributed to A2a by Tamm et al, 34 indeed belongs to A2a1 (Supplementary Figure S1). Aside from an almost identical A2a1 complete sequence harbored by an Inuit gleaned from GenBank (Supplementary Table S1), the HVS-I database also indicates a major presence of A2a1 among the Chukchi 10 and in the Aleut.…”
Section: New Findings and Interpretationmentioning
confidence: 72%
“…It is possible that members of mitochondrial haplogroups A and D in the Southwest are so infrequent (Table S1) that they do not display a similar pattern. Although mitochondrial haplogroup C is relatively common, the haplotype network of this haplogroup (SI Text) may be confounded by containing members of at least four newly described founding lineages that cannot be differentiated by D-loop sequence alone (59,62). As to the difference in pattern between the uniparentally inherited markers, Balaresque et al (63) recently discovered that the advent of farming allowed for an expansion of Neolithic males in Europe, but a similar expansion was not detected in the mtDNA.…”
Section: Resultsmentioning
confidence: 99%